Immune Infiltrates of m6A RNA Methylation-Related lncRNAs and Identification of PD-L1 in Patients With Primary Head and Neck Squamous Cell Carcinoma - Feng, Zi-Yi; Gao, Hao-Yu; Feng, Tian-Da (Frontiers in Cell and Developmental Biology, 2021)
Background: The purpose of this study was to determine the association between m6A-modified lncRNAs, immune infiltration, and PD-L1 expression in patients with primary head and neck squamous cell carcinoma (HNSCC) and the prognostic value of m6A RNA methylation-related lncRNAs in HNSCC. Methods: We downloaded the RNA-seq transcriptome data and the clinical information for HNSCC from the TCGA databases and used consensus clustering analysis to divide the samples into two groups. To identify a risk signature, least absolute shrinkage and selection operator (LASSO) analyses were conducted. the association between m6A-modified lncRNAs, immune infiltration, and PD-L1 expression were detected by using the R packages. What is more, we used cBioPortal tools to identify genomic alterations and PD-L1 mutations and Gene set enrichment analysis (GSEA) was utilized to predict downstream access of two clusters. Results: Notably, lncRNAs play significant roles in tumorigenesis and development. In total, we identified two subtypes of HNSCC according to consensus clustering of the m6A RNA methylation-related lncRNAs, and the T, grade and age were proven to be related to the subtypes. The Cox regression and LASSO analyses identified a risk signature including GRHL3-AS1, AL121845.4, AC116914.2, AL513190.1. The prognostic value of the risk signature was then proven. The selected gene PD-L1 mutations and the immune infiltration in both groups were further explored. Conclusion: Collectively, our study elucidated the important role of m6A RNA methylation- related lncRNAs in tumor microenvironment of HNSCC. The proposed m6A RNA methylation- related lncRNAs might serve as crucial mediators of tumor microenvironment of HNSCC, representing promising therapeutic targets in improving immunotherapeutic efficacy.